1985
DOI: 10.1259/0007-1285-58-692-770
|View full text |Cite
|
Sign up to set email alerts
|

Occult hydatid disease presenting as a spontaneous pneumothorax

Abstract: Pneumothorax is a rare complication of pulmonary hydatid disease and has been reported only once in Britain (Connellan et al, 1979), although it has been described in areas where the disease is endemic (Waddle, 1950; Tomalino, 1959; Bakir & Al-Omeri, 1969; Xanthakis et al, 1972). A case is described in which a patient with hydatid disease presented with a spontaneous pneumothorax. The diagnosis was not made until he underwent thoracotomy and lung biopsy following the development of secondary lung parenchym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Humans are accidental intermediate hosts infected by ingestion of food contaminated with eggs shed by dogs or foxes and are common in rural areas. Eggs hatch in the duodenum and enter the mesenteric venules and become lodged in the capillary filter bed in various organs except for hair, teeth or finger nails [5]. The most important site is liver (70%), lung (15%), kidney (3%), spleen (4%), cerebrum (2%) and heart (0.02-2%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Humans are accidental intermediate hosts infected by ingestion of food contaminated with eggs shed by dogs or foxes and are common in rural areas. Eggs hatch in the duodenum and enter the mesenteric venules and become lodged in the capillary filter bed in various organs except for hair, teeth or finger nails [5]. The most important site is liver (70%), lung (15%), kidney (3%), spleen (4%), cerebrum (2%) and heart (0.02-2%).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 2,013 patients by the Tunisian Surgical Association, the mean age was 32 years [9]. Ayadi-Kaddour et al reported a case in which the patient was 66 years old [5]. Clinical manifestations of hydatidosis in humans are variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of local pleural adhesions, a spontaneous pneumothorax results. [82][83][84] Although not common, Xanthakis and colleagues 71 found spontaneous pneumothorax as the first manifestation of illness in 3 of 91 patients with hydatid disease of the chest. If the collapsed pericyst acts as a valve, a tension pneumothorax may develop, resulting in mediastinal shift.…”
Section: Pneumothoraxmentioning
confidence: 99%
“…84 Since rupture is more often found in small than in large cysts, 71 the cause of the pneumothorax may not be readily apparent unless additional intact hydatids are demonstrated radiographically. 83,84…”
Section: Pneumothoraxmentioning
confidence: 99%